2014
DOI: 10.9790/0853-1361117120
|View full text |Cite
|
Sign up to set email alerts
|

Study of Scapular Measurements and Scapular Indices of Andhrapradesh Region

Abstract: Scapula, the triangular flat bone links the axial skeleton to the appendicular skeleton of upper limb along with clavicle. It shows modifications in its shape in the evolutionary process from quadrupeds to bipeds. Much of the changes have taken place in the infraspinous region. In the present study scapular measurements like breadth, length and infraspinous length are taken and parameters like scapular index, infraspinous index and are calculated which may help in comparative anatomy and defining the race.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
2
1
0
1
Order By: Relevance
“…Maximum Scapular Length: The mean length of scapula observed in the present study was 141.94 mm with a SD of 12.76 mm. The findings of the present study coincided with the values obtained by Singhal et al [7] in Gujarati population & Krishnaiah et al [8] in people of Nalgonda region where they found a mean length of 141.7±8.9 mm and 143.27±11.44 mm respectively. However the findings of the present study were quite different when compared to studies done by Flower W H [9] on European race where he found an average length of 155.54 mm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Maximum Scapular Length: The mean length of scapula observed in the present study was 141.94 mm with a SD of 12.76 mm. The findings of the present study coincided with the values obtained by Singhal et al [7] in Gujarati population & Krishnaiah et al [8] in people of Nalgonda region where they found a mean length of 141.7±8.9 mm and 143.27±11.44 mm respectively. However the findings of the present study were quite different when compared to studies done by Flower W H [9] on European race where he found an average length of 155.54 mm.…”
Section: Discussionsupporting
confidence: 93%
“…The mean scapular breadth found in the present study was 103.65mm with a SD of 6.82mm. These findings are very similar to those observed by Krishnaiah et al [8] [12][13][14]. All these three measurements on female glenoids were significantly lower than that reported in the present study.…”
Section: Maximum Scapular Breadthsupporting
confidence: 93%
“…Singhal 19 , Krishnaiah ve arkadaşlarının20 yaptıkları çalışmalarda sırasıyla; 73,32, 68,5 ve 73,99'dur. Çalışmamızdaki SI değeri literatüre göre daha yüksek bulunmuştur.…”
unclassified
“…Human scapula is a flat triangular shaped bone placed on posterolateral aspect of thoracic cage forming back of the shoulder girdle. The human scapula is formed of two components phylogenetically that have fused together: the (dorsal) scapula proper and the (ventral) coracoid (1). Scapula plays a significant function in the movements of shoulder girdle (2).…”
Section: Introductionmentioning
confidence: 99%